‘The Trees are the Clothes of the Church’: Ethiopian Orthodox Tewahedo Church-Forests as Spiritual Spaces of Resilience against Climate Change? - Fischer, Moritz 1961- (2024)
In times of ecological crises, Ethiopian Orthodox Tewahedo church-forests are, as many suggest, sacred spaces of resilience and restoration. The need for community forest management and sustainable use of natural resources is said to be based on an ‘eco-theology of Edenic forests’ so, we ask, What can be said about conceptually defined entanglements between the theological perspective on so-called forest-churches and the ecologically oriented perspective that applies to so-called church-forests? What is the history and the present self-understanding of this phenomenon? Does it have a global dimension? How does a sacred text like Śənä Fəṭrät, with its theocentric theology and its reference to biblical testimony, create ‘sacred spaces’ in nature? The socio-ethical dimension of these church-forests is of high concern. For this, with an interdisciplinary focus, I refer to results given by existing research on the interrelations of oriental-orthodox theology, including its miaphysite Christology. Such an understanding includes reference to church architecture, biology, sociology, and on forestry in those areas of forest-churches. So we want to understand the specific religious and cultural significance of Ethiopian Orthodox Tewahedo church-forests. The relevance of these unique sacred groves cannot easily be compared to examples in other religions. But we may at least draw conclusions from other forms of Christianity and religiosity and their interpretation of common biblical and dogmatic traditions referring to the ‘creation of God’.
Keywords: Theocentric cosmology; Sacred groves; Miaphysite Christology; Community forest management; Sacred Texts; Ethiopian Orthodox Tewahedo Church; Eco-theology; Church-forests